(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The aim of this study is to validate the ERA5 Wave Energy Flux (WEF) estimations against observational data. To that end, 0.5° x 0.5° resolution ERA5 reanalisis WEF values and corresponding data from 15 directional REDEXT buoys of Puertos del Estado surrounding the Iberian and Canary Islands’ coast covering a period of ten years (2005-2014) have been used. In this study, the Sailor diagram and its methodology [1] have been used to compare the skill of the model for a two-dimensional variable (WEF). The methodology on which the Sailor diagram is built proposes a diagram along with different statistical indices. In this particular case, WEF is a vectorial magnitude, and its zonal and meridional components (WEFx and WEFy) have been assessed at the same time. To compare the observed data with the ERA5 data, well-known indices extended to two dimensions such as RMSE, correlation and bias have been used, as well as variances of each component. Furthermore, to analyse if the WEFx and WEFy components of the ERA5 data are rotated in relation to the observations, their relative rotation angle, eccentricity, and congruence coefficient of the first EOF (Empirical Orthogonal Function) have also been examinated. This way, the analysis is extended to fully cover the dimensionality of the data. [1] Sáenz J, Carreno-Madinabeitia S, Esnaola G, González-Rojí SJ, Ibarra-Berastegi G, Ulazia A. The Sailor diagram – A new diagram for the verification of two-dimensional vector data from multiple models. Geosci Model Dev. 2020;13(7):3221–40. https://doi.org/10.5194/gmd-13-3221-2020